Adaptasi Diri Warga Binaan di Lembaga Permasyarakatan Perempuan Kelas IIA Sungguminasa - Andini, Andini; Bahfiarti, Tuti; Karnay, Sudirman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2024)
This research aims to describe the self-adaptation of inmates at the Sungguminasa Class IIA Women's Correctional Institution which can be achieved by fulfilling basic needs. This type of research is descriptive qualitative and uses observation, interviews and documentation of inmates as research informants consisting of backgrounds on different criminal cases, sentences and time spent serving their sentences. The research results show that self-adaptation efforts are achieved by fulfilling basic needs which include fulfilling physiological, psychological and social needs. Furthermore, self-adaptation is achieved by implementing habits and skills that can and encourage them to gain self-confidence in arranging a new life. Furthermore, self-introduction efforts by recognizing and knowing each other's weaknesses and strengths as well as self-adaptation are achieved by self-acceptance by accepting themselves as prisoners free from shame and worry about other people's views of them.